Optimalisasi Manajemen Usaha pada Industri Jasa Penataan Rambut Crown Barbershop - Ahmad Taufiqurrahman Asy’ari; Abdullah As Shoib; Agus Hermawan; Agung Winarno (Pusat Riset dan Inovasi Nasional, 2025)
Crown Barbershop is an SME engaged in men's hair care and styling services in Cerme, Gresik, which has only been operating since June. This study aims to analyze the strengthening of Crown Barbershop's competitiveness through marketing optimization, service quality improvement, human resource management, and financial system improvement. The research method used is descriptive qualitative through observation and direct interviews with the business owner. The results show that digital marketing based on Instagram and TikTok needs to be optimized with more creative content strategies. In addition, service quality improvement through consistent operational standards also needs to be implemented. In terms of HR, barber skill training is essential to keep up with the latest hairstyle trends. Meanwhile, in the financial aspect, a more structured recording system is needed to ensure business sustainability. This study concludes that the synergy of these four managerial aspects can increase the competitiveness of Crown Barbershop amid increasingly competitive barbershop industry competition.